The Role of Hydrogen for Sulfurimonas denitrificans’ Metabolism - Han, Yuchen (Public Library of Science, 2014)
Sulfurimonas denitrificans was originally isolated from coastal marine sediments. It can grow with thiosulfate and nitrate or sulfide and oxygen. Recently sequencing of its genome revealed that it encodes periplasmic and cytoplasmic [NiFe]-hydrogenases but the role of hydrogen for its metabolism has remained unknown. We show the first experimental evidence that S. denitrificans can indeed express a functional hydrogen uptake active hydrogenase and can grow on hydrogen. In fact, under the provided conditions it grew faster and denser on hydrogen than on thiosulfate alone and even grew with hydrogen in the absence of reduced sulfur compounds. In our experiments, at the time points tested, the hydrogen uptake activity appeared to be related to the periplasmic hydrogenase and not to the cytoplasmic hydrogenase. Our data suggest that under the provided conditions S. denitrificans can grow more efficiently with hydrogen than with thiosulfate.